Attenuation of the plasma volume response to crystalloid fluid used for goal-directed fluid therapy - Robert G. Hahn; Terry O’Brien (Annals of Intensive Care)
Abstract Background Goal-directed fluid therapy uses repeated bolus infusions of crystalloid or colloid fluid to increase the plasma volume for the purpose of challenging the patient’s position on the Frank-Starling curve. Each bolus is assumed to increase cardiac preload to the same degree. We examined whether this view is reasonable by simulating the plasma volume responses to crystalloid and colloid fluid. For this purpose, the volume kinetics of crystalloid fluid was characterized in 103 anaesthetized patients while parameters for colloid (hydroxyethyl starch) were taken from the literature. Simulations focused on the plasma volume response to 3 bolus infusions of 4 mL/kg of crystalloid and 2–4 mL/kg of colloid over 7 min. The boluses were separated by a free interval of 5 min to allow hemodynamic assessment. Results Crystalloid fluid showed attenuation of the plasma volume response to repeated bolus infusions. The second and third bolus increased the plasma volume by only 51 and 36% as much as the first one. Attenuation also occurred when the boluses were preceded by a constant-rate infusion of 5 mL/kg/h or 10 mL/kg/h of crystalloid over 60 min, while placing the patient in the Trendelenburg body position (head down) reduced the attenuation. Bleeding increased the plasma volume responses, but attenuation still occurred. Colloid fluid did not show attenuation. Conclusion Attenuation of the plasma volume response to bolus infusions of crystalloid fluid occurs. The second and third bolus might not increase cardiac preload enough to allow a correct diagnosis of fluid responsiveness. This problem is not shared by colloid fluid.